2021
DOI: 10.3389/fvets.2021.623899
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage as an Alternative to Antibiotics Promotes Growth Performance by Regulating Intestinal Inflammation, Intestinal Barrier Function and Gut Microbiota in Weaned Piglets

Abstract: This study aimed to investigate the effects of dietary bacteriophage supplementation on growth performance, intestinal morphology, barrier function, and intestinal microbiota of weaned piglets fed antibiotic-free diet. A total of 120 weaned piglets were allotted to four dietary treatments with five pens/treatment and six piglets/pen in a 21-d feeding trial. The control diet was supplemented with 25 mg/kg quinocetone and 11.25 mg/kg aureomycin in the basal diet, while the three treatment diets were supplemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 63 publications
(81 reference statements)
2
50
1
Order By: Relevance
“…It has been shown that in Salmonella-infected chickens treated with bacteriophages, mRNA expression of IFN-γ, TLR4, and IL-4 in the jejunum, as well as IFN-γ, HSP27, and TNF-α in the liver were decreased relative to the Salmonella-infected but non-treated control [77]. On the other hand, Zeng et al [78] tested the effects of bacteriophage supplementation on TLR2, TLR4, and TLR9 levels in piglets and found that the supplementation of 400 mg/kg bacteriophages increased the mRNA expression of tested TLRs in the jejunum. These results proved that bacteriophages activated the immune system by regulating the inflammatory response through TLRs [78].…”
Section: Foreign Particles Vs Innate Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that in Salmonella-infected chickens treated with bacteriophages, mRNA expression of IFN-γ, TLR4, and IL-4 in the jejunum, as well as IFN-γ, HSP27, and TNF-α in the liver were decreased relative to the Salmonella-infected but non-treated control [77]. On the other hand, Zeng et al [78] tested the effects of bacteriophage supplementation on TLR2, TLR4, and TLR9 levels in piglets and found that the supplementation of 400 mg/kg bacteriophages increased the mRNA expression of tested TLRs in the jejunum. These results proved that bacteriophages activated the immune system by regulating the inflammatory response through TLRs [78].…”
Section: Foreign Particles Vs Innate Immune Responsementioning
confidence: 99%
“…On the other hand, Zeng et al [78] tested the effects of bacteriophage supplementation on TLR2, TLR4, and TLR9 levels in piglets and found that the supplementation of 400 mg/kg bacteriophages increased the mRNA expression of tested TLRs in the jejunum. These results proved that bacteriophages activated the immune system by regulating the inflammatory response through TLRs [78]. In a recent study, Gogokhia et al [76] showed that bacteriophages activated the synthesis of IFN-γ through TLR9.…”
Section: Foreign Particles Vs Innate Immune Responsementioning
confidence: 99%
“…Antibiotics have been widely used in pig feed, especially in weaned piglets to promote growth, treat infectious diseases, and control the gut microbiota ( Hu et al, 2020 ; Zeng et al, 2021 ). However, antibiotics not only affect the target microorganisms but also the microbial community, especially the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Using bacterial viruses, namely bacteriophages, is also a promising alternative which has been increasingly tried on pigs and seems to work well to reduce the load of pathogens and to increase growth [136][137][138]. For example, Zeng et al have shown that adding a cocktail of phages globally targeting Salmonella, E. coli, C. perfringens and S. aureus to pig feed significantly increased the average daily gain and feed intake and decreased the feed/gain ratio and the risks of diarrhea in weanling piglets [137].…”
Section: Alternatives To Antibioticsmentioning
confidence: 99%